Towards the Future Generation Rights in Indonesian Law to Make Justice in the Inter Generation in the Environmental Sector - Negara, Purnawan D; Handoko, Widhi (International Conference of Moslem Society, 2018)
Efforts on environmental protection in Indonesia are very advanced and progressive, this can be seen from the development of Indonesia democracy which based on ecological (ecocracy) which has given legal rights to the nature/environment in the form of constitutional rights and human rights from nature/environment. The recognition is a form of balancing of the provision of human rights given which guarantees on a good and healthy environment. The ecocracy implementation is embodied in the development policy in Indonesia based on the principle of sustainable development, which is â€œdevelopment that meets the needs of the present without compromising the ability of future generations to meet their own needsâ€. This policy has triggered the notion that if nature and the present generation have the legal right to a good and healthy environment then future generations can also have the same legal rights. It has not been existed in Indonesian law. The effort to go there is not utopian because Indonesian civil law has recognized the rights of future generations through Article 2 of the KUHPer, as well as by the values â€‹â€‹of adat law have recognized the existence of natural rights, as well as by Islamic values â€‹â€‹(as the largest religion) has provided the basis that the creation of the universe is reserved for human welfare (assigned to be the caliphate), the embodiment of the future generations can be seen from the blowing of the spirits to humans by God. The law is not in a hollow space, so the development of law in Indonesia should not be uprooted from its social base in order not to lose its meaning and power in society, future generation rights is not something new for Indonesian society, therefore the development of environmental law needs to drive to make it exist for environmental protection.